In touch: Cardiac and respiratory patterns synchronize during ensemble singing with physical contact - Lange, Elke B.; Omigie, Diana; Trenado, Carlos; Müller, Viktor; Wald-Fuhrmann, Melanie; Merrill, Julia (Frontiers in Human Neuroscience, 2022)
Musical ensemble performances provide an ideal environment to gain knowledge about complex human interactions. Network structures of synchronization can reflect specific roles of individual performers on the one hand and a higher level of organization of all performers as a superordinate system on the other. This study builds on research on joint singing, using hyperscanning of respiration and heart rate variability (HRV) from eight professional singers. Singers performed polyphonic music, distributing their breathing within the same voice and singing without and with physical contact: that is touching each other’s shoulder or waist. The idea of singing with touch was motivated by historical depictions of ensemble performances that showed singers touching each other. It raises the question of the potential benefit of touch for group performances. From a psycho-physiological point of view, physical contact should increase the synchronization of singing coordination. The results confirm previous findings on synchronization of respiration and HRV during choir singing and extend those findings to a non-homophonic musical repertoire while also revealing an increase in synchronization in respiration during physical contact. This effect was significant across different frequency ranges. The effect of physical contact was stronger when all singers were singing in comparison to the partial ensemble. Importantly, the synchronization could not be fully explained by the singing action (i.e., singing the same voice, or singing versus listening) or by the standing position or touch. This finding suggests a higher level of organization of all singers, forming a superordinate system.